2012
DOI: 10.1111/j.1523-5378.2012.00954.x
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Association between Helicobacter pylori CagA EPIYA and Multimerization Motifs with Cytokeratin 18 Cleavage Rate during Early Apoptosis

Abstract: Background and Aims:  Helicobacter pylori is a highly diverse pathogen, which encounters epithelial cells as the initial defense barrier during its lifelong infection. The structure of epithelial cells can be disrupted through cleavage of microfilaments. Cytokeratin 18 (CK18) is an intermediate filament, the cleavage of which is considered an early event during apoptosis following activation of effector caspases. Methods:  Helicobacter pylori strains were isolated from 76 dyspeptic patients. cagA 3’ variable r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 45 publications
1
21
0
1
Order By: Relevance
“…Western CagA consists of a combination of EPIYA-A and -B, followed by various number of EPIYA-C repeats (up to five EPIYA-C segments), whereas East Asian CagA contains a combination of EPIYA-A, -B, and -D segments (Hatakeyama, 2011;Jones et al, 2010). In the case of our strains, the Western type cagA (EPIYA-ABC) was the most prevalent variant in all of the patient groups studied, which is consistent with the previous studies from Iran (Saberi et al, 2012;Shokrzadeh et al, 2010;Vaziri et al, 2013). The C-terminal structure of CagA among our strains is also similar with the strains isolated from other countries including Sweden (Monstein et al, 2010), Turkey (Salih et al, 2010), Colombia (Sicinschi et al, 2010) and USA (Ogorodnik and Raffaniello, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Western CagA consists of a combination of EPIYA-A and -B, followed by various number of EPIYA-C repeats (up to five EPIYA-C segments), whereas East Asian CagA contains a combination of EPIYA-A, -B, and -D segments (Hatakeyama, 2011;Jones et al, 2010). In the case of our strains, the Western type cagA (EPIYA-ABC) was the most prevalent variant in all of the patient groups studied, which is consistent with the previous studies from Iran (Saberi et al, 2012;Shokrzadeh et al, 2010;Vaziri et al, 2013). The C-terminal structure of CagA among our strains is also similar with the strains isolated from other countries including Sweden (Monstein et al, 2010), Turkey (Salih et al, 2010), Colombia (Sicinschi et al, 2010) and USA (Ogorodnik and Raffaniello, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…The microarray results showed that KRT18 was upregulated approximately 3.5-fold by EGR1 induction. KRT18, together with KRT8 (CK8), is an extremely important tumor marker in clinical diagnosis that is expressed in single-layer epithelial tissues of the body and is involved in carcinogenesis1819. The relationship between EGR1 and KRT18 was confirmed by dual luciferase assay.…”
Section: Resultsmentioning
confidence: 98%
“…GPCs of 2 donors were then evaluated as a model for extended infection of H. pylori . For this purpose, we selected a hypervirulent clinical strain of H. pylori , which had been previously evaluated for its virulence and toxicity by vacuolation and hummingbird functional assays. Considering the fact that H. pylori are gram‐negative microorganisms with a significant content of LPS, we sought to stain the bacteria, prior to GPC infection.…”
Section: Resultsmentioning
confidence: 99%